Mechanism of allosteric propagation across a β‐sheet structure investigated by molecular dynamics simulations. Issue 7 (9th May 2016) - Interlandi, Gianluca; Thomas, Wendy E.
ABSTRACT: The bacterial adhesin FimH consists of an allosterically regulated mannose‐binding lectin domain and a covalently linked inhibitory pilin domain. Under normal conditions, the two domains are bound to each other, and FimH interacts weakly with mannose. However, under tensile force, the domains separate and the lectin domain undergoes conformational changes that strengthen its bond with mannose. Comparison of the crystallographic structures of the low and the high affinity state of the lectin domain reveals conformational changes mainly in the regulatory inter‐domain region, the mannose binding site and a large β sheet that connects the two distally located regions. Here, molecular dynamics simulations investigated how conformational changes are propagated within and between different regions of the lectin domain. It was found that the inter‐domain region moves towards the high affinity conformation as it becomes more compact and buries exposed hydrophobic surface after separation of the pilin domain. The mannose binding site was more rigid in the high affinity state, which prevented water penetration into the pocket. The large central β sheet demonstrated a soft spring‐like twisting. Its twisting motion was moderately correlated to fluctuations in both the regulatory and the binding region, whereas a weak correlation was seen in a direct comparison of these two distal sites. The results suggest a so called "population shift" model whereby binding of the lectin domain to either the pilin domain or mannose locks the β sheet in a rather twisted or flat conformation, stabilizing the low or the high affinity state, respectively. Proteins 2016; 84:990–1008. © 2016 The Authors. Proteins: Structure, Function, and Bioinformatics Published by Wiley Periodicals, Inc.